FAKTOR RISIKO KEJADIAN DIARE AKUT DEHIDRASI RINGAN/ SEDANG DAN DEHIDRASI BERAT PADA ANAK USIA 6-24 BULAN DI RSUD TUGUREJO SEMARANG - Sakti Widyaningsih, Tri (Jurnal Ilmu dan Teknologi Kesehatan, 2012)
Event Risk Factors Of Acute Diarrhea Dehydration Of Light / Medium Dehydration And Weight In Children 6-24 Months In Hospital Tugurejo SemarangThis study aimed to identify risk factors for acute diarrheal dehydration mild / moderate and severe dehydration in children aged 6-24 months Tugurejo Public Hospital in Semarang. This study used a descriptive study with cross sectional correlation. Sample study was total 135 respondents. The results indicated the factors that related to the incidence of acute diarrhea is nutritional status (p = 0.031), hand hygiene and nail (p = 0.000), maternal education (p = 0.009), knowledge of mothers (p = 0.02), mothers habit of washing hands before feeding children (p = 0.012), use of water resources (p = 0.004), with septitank latrine distance (p = 0.014) and family income (p = 0.001). The dominant risk factors on the incidence of acute diarrhea are immunized against measles, maternal education and the use of water resources. Keywords: risk factors, acute diarrhea dehydration, children aged 6-24 months